(Re)-Examining the Influence of Program Placement on the Academic Achievement of Students with Learning Disabilities - McKibbin, Steven (Université d'Ottawa / University of Ottawa, 2020)
This study explored the relationship between several variables known to influence achievement in Canadian Grade 6 students with Learning Disabilities (LD) who received instruction in either a regular class or specialized program placement. The main independent variable was program placement while the influence of four other independent variables was explored (i.e., level of academic need; prior achievement; socioeconomic status and sex). The dependent variable was a standardized, large-scale assessment of achievement. Hierarchical multiple regression was conducted on a secondary data file in order to address the following research questions: i) Does placement in a regular or specialized program influence the educational outcomes for Grade 6 students with LD, after controlling for the influence of prior achievement in Grade 3?; ii) Is there a relationship between the sociodemographic variables of sex and/or socioeconomic status and achievement for students with LD placed in either a regular or specialized program?; and iii) What influence does the student’s level of academic need have on achievement, beyond program placement, and after controlling for the influence of the other variables in the model? Results revealed that the variables of program placement and prior achievement were significant predictors of scholastic success only when the level of academic need variable was not taken into account. When the follow-up analysis focused on a relatively matched group of students with similar academic need, none of the predictors in the regression model significantly influenced achievement -- including program placement. These results provide important insight into the nuanced relationship of the ecological variables known to affect learning in students with LD placed in regular or specialized programs for instruction. Implications are discussed for stakeholders in Ontario’s public education system in terms of the optimum service delivery model for students with LD, and the inclusive education debate in Canada and abroad.
Keywords: Learning Disabilities; Program Placement; Inclusive Education; K-12; EQAO; Multiple Imputation; Hierarchical Regression; Special Education